Facile Synthesis of Propranolol and Novel Derivatives - Vy Anh Tran; Nguyen Hai Tai Tran; Long Giang Bach; Trinh Duy Nguyen; Thi Thuong Nguyen; Tan Tai Nguyen; Thi Anh Nga Nguyen; The Ky Vo; Thu-Thao Thi Vo; Van Thuan Le (Journal of Chemistry)
Propranolol is one of the first medications of the beta-blocker used for antihypertensive drugs. This study reports the facile route for the synthesis of propranolol and its novel derivatives. Herein, propranolol synthesis proceeded from 1-naphthol and isopropylamine under mild and less toxic conditions. Novel propranolol derivatives were designed by reactions of propranolol with benzoyl chloride, pyridinium chlorochromate, and n-butyl bromide through esterification, oxidation reduction, and alkylation, respectively. The isolation and purity of compounds were conducted using column chromatography and thin-layer chromatography. Mass spectrometry and 1H-NMR spectroscopy were applied to identify new compounds structure. Propranolol derivatives from 2-chlorobenzoyl chloride (compound 3), 2-fluorobenzoyl chloride (compound 5), and especially acetic anhydride (compound 6) manifested high yields and significantly increased water solubility. Six semisynthetic propranolol derivatives promise to improve antioxidative and biological activities.